2019
DOI: 10.1038/s41598-019-47127-2
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting Ordered States, Local Equilibrium-like Domains, and Broken Ergodicity in a Non-turbulent Rayleigh-Bénard Convection at Steady-state

Abstract: A challenge in fundamental physics and especially in thermodynamics is to understand emergent order in far-from-equilibrium systems. While at equilibrium, temperature plays the role of a key thermodynamic variable whose uniformity in space and time defines the equilibrium state the system is in, this is not the case in a far-from-equilibrium driven system. When energy flows through a finite system at steady-state, temperature takes on a time-independent but spatially varying character. In this study, the conve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 98 publications
(149 reference statements)
1
15
0
Order By: Relevance
“…The results are then compared with an experimental system, the Rayleigh-Bénard convection for different fluid mixtures at varying Rayleigh numbers (10 3 − 10 6 ). Our study indicates that the nature of emergent order, and the second statistical moment of the respective intrinsic variables follow similar trends across the three systems [14][15][16].…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…The results are then compared with an experimental system, the Rayleigh-Bénard convection for different fluid mixtures at varying Rayleigh numbers (10 3 − 10 6 ). Our study indicates that the nature of emergent order, and the second statistical moment of the respective intrinsic variables follow similar trends across the three systems [14][15][16].…”
Section: Introductionsupporting
confidence: 53%
“…We are still unsure of the fact that how the fit functions from the two tails merge into one another. In some of our recent works we discuss the presence of a mixture of local equilibrium regions in the Rayleigh-Bénard convection which describes the bimodal nature of the thermal fluctuations [14][15][16]. To conclude, in the mean-field Kuramoto model the final synchronous state being unique allows for the existence of a sharply peaked delta-type distribution, which in reality is best illustrated by a Lorentizian fit.…”
Section: Rayleigh-bénard Convectionmentioning
confidence: 95%
See 1 more Smart Citation
“…Since the focus of this study lies in the search for simple modeling tools to understand pattern formation in a complex system, the choice of our model systems is not random. In our previous studies, we had shown how the mean temperature of the top layer of the fluid film bifurcates into ‘hot’ and ‘cold’ domains as a steady-steady is achieved in a non-turbulent Rayleigh–Bénard system [ 19 , 20 , 21 ]. The coexistence of two states, hot and cold, draws similarities to the Ising model which has been successfully used to understand many two-state systems/processes.…”
Section: Introductionmentioning
confidence: 99%
“…While the temporal study allows us to envision the evolution of order in the system, the spatial study lets us visualize how order is spatially distributed through emergent length-scales. One can find more details on the study: the experiments and the analyses here [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%